Polymorphisms of IGF-1 Gene in Indonesian Local Goat Reared Under Smallholder Farmers in Sulawesi Region - Rahim, Lellah; Dagong, Muhammad Ihsan Andi; Bugiwati, Sri Rachma Aprilita; Purnomo, Nurul (Faculty of Agriculture, 2024)
ABSTRACT. The objective of this study was to determine the allele frequency of IGF-1 in Kacang and Peranakan Ettawa goats in Indonesia. The DNA samples were extracted from the blood of 105 heads of goats and collected from the South Sulawesi and West Sulawesi provinces. The IGF-1 target was amplified using the PCR-RFLP method. Two allele variants (A and B) and three genotypes of the IGF-1 gene (AA, AB, and BB) have been identified in the local goat population. Allele frequencies of IGF-1 were A (0.81) and B (0.19) in the total population of local goats. Allele A is the most common allele in both the Kacang and Peranakan Ettawa goat populations, with the highest frequency found in the Kacang population (0.87). The most common genotype is genotype AA, with the highest frequency in the Kacang population (0.75). The observed and expected heterozygosity were 0.276 and 0.303, respectively. The population of local goats in these regions was in Hardy-Weinberg equilibrium. The conclusion of this research is that the IGF-1 gene in local goats in the Sulawesi region is polymorphic and this diversity information can be used for association studies with growth traits, litter size, and twinning rate.(Polimorpisme gen IGF-1 pada populasi kambing lokal Indonesia yang dipelihara oleh peternak kecil di daerah Sulawesi)ABSTRAK. Penelitian ini bertujuan untuk mengetahui frekuensi alel IGF-1 pada kambing Kacang dan Peranakan Ettawa di Indonesia. Sampel DNA diambil dari darah 105 ekor kambing dan dikumpulkan dari Provinsi Sulawesi Selatan dan Sulawesi Barat. Target IGF-1 diamplifikasi menggunakan metode PCR-RFLP. Dua varian alel (A dan B) dan tiga genotipe gen IGF-1 (AA, AB, dan BB) telah diidentifikasi pada populasi kambing lokal. Frekuensi alel IGF-1 adalah A (0,81) dan B (0,19) pada total populasi kambing lokal. Alel A merupakan alel yang paling banyak ditemukan baik pada populasi kambing Kacang maupun kambing Peranakan Ettawa, dengan frekuensi tertinggi terdapat pada populasi Kacang (0,87). Genotipe yang paling umum adalah genotipe AA, dengan frekuensi tertinggi pada populasi Kacang (0,75). Heterozigositas yang diamati dan diharapkan adalah 0,276 dan 0,303, masing-masing. Populasi kambing lokal di wilayah ini berada dalam keseimbangan Hardy-Weinberg. Kesimpulan yang dihasilkan adalah bahwa gen IGF-1 pada kambing lokal yang dipelihara oleh peternak di wilayah Sulawesi bersifat polimorfik dan informasi keragaman ini dapat digunakan untuk studi asosiasi dengan sifat pertumbuhan, litter size dan kelahiran kembar.